2021
DOI: 10.3390/genes12111824
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Landscape of Inherited Retinal Diseases in a Mexican Cohort: Genes, Mutations and Phenotypes

Abstract: In this work, we aimed to provide the genetic diagnosis of a large cohort of patients affected with inherited retinal dystrophies (IRDs) from Mexico. Our data add valuable information to the genetic portrait in rare ocular diseases of Mesoamerican populations, which are mostly under-represented in genetic studies. A cohort of 144 unrelated probands with a clinical diagnosis of IRD were analyzed by next-generation sequencing using target gene panels (overall including 346 genes and 65 intronic sequences). Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…This is a higher incidence than has been identified in other populations. 10,12 Studies have also identified BBS7 mutations in Spanish and Mexican cohorts. 12 However, the p. Thr211Ile variant has not been previously identified in other populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a higher incidence than has been identified in other populations. 10,12 Studies have also identified BBS7 mutations in Spanish and Mexican cohorts. 12 However, the p. Thr211Ile variant has not been previously identified in other populations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that mutations in the CRB1 gene are one of the major contributors to RP in the Mexican population. 10 Mutations in CRB1 contributed to 7% of pathogenic mutations associated with inherited retinal dystrophies. 10 In our cohort, mutations in CRB1 were associated with 11% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RAB28 null and hypomorphic alleles cause autosomal recessive cone-rod dystrophy (arCRD) with eight pathogenic alleles attributed to date. [18][19][20][21][22][23] In Caenorhabditis elegans, we have shown that Rab28 is an intraflagellar transport (IFT) and BBSome-associated ciliary protein, 24 which regulates extracellular vesicle biogenesis in a subset of ciliated neurons. 25 In addition, we employed zebrafish knockout and transgenic reporter models to probe Rab28's localization and, we previously described the localization, GTP/GDP nucleotide regulation, and a protein interactome of Rab28 in cone photoreceptors.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, the small ciliary GTPase Rab28 was identified as the first Rab GTPase associated with human cone‐rod dystrophy (CRD). RAB28 null and hypomorphic alleles cause autosomal recessive cone‐rod dystrophy (arCRD) with eight pathogenic alleles attributed to date 18‐23 . In Caenorhabditis elegans , we have shown that Rab28 is an intraflagellar transport (IFT) and BBSome‐associated ciliary protein, 24 which regulates extracellular vesicle biogenesis in a subset of ciliated neurons 25 .…”
Section: Introductionmentioning
confidence: 99%